Tracing the Evolution of Carbon Tax Research: A Bibliometric Analysis of Global Publication Trends - Siti Maghfiroh; Aprilia Nastiti Rahayu (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2025)
Greenhouse gas (GHG) emissions have increased in all sectors since 2010. A carbon tax is one of the policies that tackle carbon emissions. Research on the carbon tax is growing along with climate change mitigation commitments. This study aims to identify the historical development of carbon tax literature and map future research directions using bibliometric methods. This research tries to answer questions related to the trends and historical development of carbon tax literature from 2010-2024. This research uses the Scopus and NVivo databases as additional tools to justify the articles used. This research applied the PRISMA protocol and bibliometric analysis approach. The Scopus database was explored to analyze trends, co-occurrence, co-authorship, co-citation, citation analysis of 2,406 articles, with publication years 2010-2024. The keyword